Some Thoughts on Operationalizing the Concept of Sufficiency in Efficiency Analysis - Peters, Malte L; Zelewski, Stephan (International Journal of Management and Sustainability, 2018)
The concept of sufficiency is rarely acknowledged in mainstream business economics and has not been addressed so far in the literature on efficiency analysis. In this paper, satisficing levels as known from the Efficiency Analysis Technique With Output Satisficing (EATWOS) and from its extension Efficiency Analysis Technique With Input and Output Satisficing (EATWIOS) are suggested to operationalize sufficiency in efficiency analysis. Moreover, a simple data transformation approach is proposed in order to use satisficing levels in other efficiency analysis techniques, particularly in the widely used Data Envelopment Analysis (DEA).